The Effect of Muntingia calabura (Kersen) Leaf Decoction as an Antidiabetic on Blood Sugar Levels Among Type II Diabetes Mellitus Patients - Ika Melina; Silvia Wagustina (JAND: Journal of Applied Nutrition and Dietetic, 2022)
Diabetes is a very high-prevalence metabolic disease characterized by increased blood sugar levels and disorders in the metabolism of carbohydrates, fats, and proteins due to insulin deficiency. This disease can also be treated through non-pharmacological treatment or herbal remedies, including by consuming the Muntingia (kersen) leaves decoction. Muntingia leaves contain flavonoids and saponins which are active antidiabetic substances functioning as inhibitors of the A-glucosidase enzymes. This study aims at determining the effect of Muntingia leaves decoction on blood sugar levels among Type II Diabetes patients in Pante Gajah, Peusangan, Bireuen. The study uses a quasi-experimental research design with treatment and controlled groups. 26 sample patients were chosen by total sampling techniques. Furthermore, the research variables are blood sugar levels (dependent variable) and Muntingia leaves decoction (independent variables). This study was done on 24-31 March 2022 within the scope of the Peusangan Community Health Center. The data were then analyzed by using an independent and dependent T-test. The results of the dependent test in the treatment group before consuming the decoction is 208.04 mg/dl and 180.92 after the treatment, the decrease is 27.12 mg/dl. The results of the independent test in the treatment group before consuming the decoction are 190.85 mg/dl on average and 144.69 mg/dl after the treatment, the decrease is 46.16 mg/dl. In the controlled group is 225.23 mg/dl before the treatment and 217.15 mg/dl after the treatment, the decrease is 8.08 mg/dl. The Muntingia leaves decoction has a significant effect on blood sugar levels.